Biodegradação do pesticida piretroide gama-cialotrina por fungos da Gruta do Catao - Rigolin, Fábio Rocha (Universidade Federal de São Carlos, 2019)
The contamination of agricultural lands by pesticides, their overuse and toxicity to many non-target organisms cause serious environmental problems. Therefore, the development of bioremediation methods for distinct active ingredients, such as pyrethroids, is primordial. In this work, the biodegradation of gamma-cyhalothrin (GCH) by fungi from the cave Gruta do Catão was investigated. Experiments were conducted with different fungi strains (Aspergillus ustus CBMAI 1894, Talaromyces brunneus CBMAI 1895 and Aspergillus sp. CBMAI 1926) in 2% Malt liquid medium with 300 mg L-1 of GCH in triplicate employing a validated method. All strains biodegraded this insecticide and the most efficient was Aspergillus ustus with a degradation rate of approximately 50% of the initial GCH concentration in 21 days of experiment. We also conducted an experimental design testing three variables: temperature (25-35 degrees), pH (5,5– 8,5) and pesticide concentration (50-550 mg L-1) being the temperature and pesticide concentration were those that most influenced the biodegradation. So, we concluded that cave fungi biodegraded GCH and can be employed in future studies for enzymatic characterization and bioremediation of contaminated environments.
Biodegradation of the pyrethroid pesticide gamma-cyhalothrin by Gruta do Catao fungi
Keywords: Aspergillus ustus; Biorrremediação; Cialotrina; Inseticida; Contaminação; Talaromyces brunneus; Bioremediation; Contamination; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA